MODEL PERSAMAAN STRUKTURAL DENGAN ESTIMASI MODEL KUADRAT TERKECIL TERTIMBANG - , SUKAMTA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The usual statistical methods and techniques canât accommodate the presence of latent variables which often occur in the model of social, economic and psychologiesâ research. Stuctural Equation Modelling Analysis is one of latent variable modelling techniques. This research studies recursive structural equation modelling with path analysis, identification model, determination of suitability functions, estimation procedure and evaluation model. The model proposed in this case study is the influence of peer interaction and student-teacher interaction in MTs N Jatimulyo, Kulon Progo, Yogyakarta. The result is structural analysis model supported by data. In this case the peer interaction influences the student studying motivation with the statistic value 2,39